REGULAR AEROBIC EXERCISE ENHANCES MEMORY AND COGNITION- A REVIEW - Dr.G.Sridevi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Aerobic exercise is the type of exercise done through walking, jogging, cycling, stair climbing, rowing or swimming. It increases the stroke volume, improves cardiovascular efficiency. It increases the respiratory rate and efficiency of breathing muscles of respiration. It also increases the musculoskeletal efficacy and strengthens muscles, tendons, ligaments and bones. Regular physical exercise improves the thinking capacity and memory skills of individuals. They denoted that pumping of heart during exercise and excess sweating increases the boosting of the hippocampal size and improves verbal learning and memory. Another study evaluated the preferred mode of exercise to improve brain ?s cognition was physical training by aerobic compared to strengthening exercises. Aerobic exercise may be preferable over balance training done through coordination, balance and flexibility exercises. Neurotransmitters like serotonin and acetylcholine levels are raised in exercising brains of rats and the medial septal GABAergic neurons play a key role in influencing the exercise induced cognitive processes. This exercise strategy offers significant neuroprotection, neuron survival and synaptic plasticity.